Validation of Genome-Wide Intervertebral Disk Calcification Associations in Dachshund and Further Investigation of the Chromosome 12 Susceptibility Locus - Mogensen, Mette Sloth; Scheibye-Alsing, Karsten; Karlskov-Mortensen, Peter; Proschowsky, Helle F.; Jensen, Vibeke F.; Bak, Mads; Tommerup, Niels; Kadarmideen, Haja N.; Fredholm, Merete (Frontiers in Genetics, 2012)
Herniation of the intervertebral disc is a common cause of neurological dysfunction in the dog, particularly in the Dachshund. Using the Illumina CanineHD BeadChip, we have previously identified a major locus on canine chromosome 12 nucleotide positions 36,750,205-38,524,449 that strongly associates with intervertebral disc calcification in Danish wire-haired Dachshunds. In this study, targeted resequencing identified two synonymous variants in MB21D1 and one in the 5’-untranslated region of KCNQ5 that associates with intervertebral disc calcification in an independent sample of wire-haired Dachshunds. Haploview identified seven linkage disequilibrium blocks across the disease associated region. The effect of haplotype windows on disc calcification shows that all haplotype windows are significantly associated with disc calcification. However, our predictions imply that the causal variant(s) are most likely to be found between nucleotide 36,750,205-37,494,845 as this region explains the highest proportion of variance in the dataset. Finally, we develop a risk prediction model for wire-haired Dachshunds. We validated the association of the chromosome 12 locus with disc calcification in an independent sample of wire-haired Dachshunds and identify potential risk variants. Additionally, we estimated haplotype effects and set up a model for prediction of disc calcifications in wire-haired dachshunds based on genotype data. This genetic prediction model may prove useful in selection of breeding animals in future breeding programs